Knowledge and Practice of Documentation Techniques among Staff Nurses - Gurung, Nirmala (Journal of College of Medical Sciences-Nepal, 2022)
Introduction Nurses are the backbone of health care systems. They are have to deal with documentation process regularly.There may be good knowledge and poor practice about documentation.The objective of the study is to find out knowledge and practice of documentation among staff nurses. Methods A descriptive cross-sectional study was conducted on staff nurses of a College of Medical Sciences- Teaching hospital between, after taking ethical approval from the Institutional Review Committee. A purposive sampling method was used and sample size was calculated to be 200. A structured questionnaire was used to collect the demographic details and knowledge and practice of documentation. Data was analyzed using statistical package for the social sciences version 20. Point estimate at 95% Confidence Interval was calculated along with frequency and percentage for binary data. Results The knowledge of documentation was seen adequate among 150(75%) staff nurses. The practice of documentation was seen poor 188(94%) among staff nurses. Conclusions The prevalence of adequate knowledge and poor practice is more in our study which is similar to other studies done in similar settings. Therefore, there is need of inservice education among staff nurses, thereby reaching a better patient care and safeguarding them from legal issues.